The Impact Of English Communication On Transportation Safety Practices - Marudut Bernadtua Simanjuntak (International Journal of Educational Development, 2024)
This research explores the critical role of English communication in promoting safety within the transportation industry. Through qualitative analysis of 100 cadets studying multimodal transportation, logistics, transportation safety, and law and road management, the study examines the impact of language barriers on safety incidents and proposes strategies for enhancing safety outcomes through improved communication. The findings highlight the significant contribution of communication breakdowns to safety incidents in transportation operations, underscoring the need for effective communication strategies. The research recommends the development of tailored training programs that integrate language proficiency with sector-specific safety knowledge, as well as the inclusion of cultural awareness training and the integration of communication technologies to enhance communication effectiveness. The study also identifies the positive impact of improved English communication on safety outcomes, suggesting that enhanced communication skills can mitigate safety risks and improve overall operational efficiency. By implementing these recommendations and prioritizing continuous professional development, transportation stakeholders can improve communication strategies and enhance safety practices within the industry.